Interplanetary origins of moderate (−100 nT < Dst ≤ −50 nT) geomagnetic storms during solar cycle 23 (1996–2008). Issue 1 (16th January 2013) - Echer, E.; Tsurutani, B. T.; Gonzalez, W. D.
Abstract : [1] The interplanetary causes of 213 moderate‐intensity (−100 nT < peak Dst ≤ −50 nT) geomagnetic storms that occurred in solar cycle 23 (1996–2008) are identified. Interplanetary drivers such as corotating interaction regions (CIRs), pure high‐speed streams (HSSs), interplanetary coronal mass ejections (ICMEs) of two types [those with magnetic clouds (MCs) and those without (nonmagnetic cloud or ICME_nc)], sheaths (compressed and/or draped sheath fields), as well as their combined occurrence were identified as causes of the storms. The annual rate of occurrence of moderate storms had two peaks, one near solar maximum and the other in the descending phase, around 3 years later. The highest rate of moderate storm occurrence was found in the declining phase (25 storms year −1 ). The lowest occurrence rate was 5.7 storms year −1 and occurred at solar minimum. All moderate‐intensity storms were associated with southward interplanetary magnetic fields, indicating that magnetic reconnection was the main mechanism for solar wind energy transfer to the magnetosphere. Most of these storms were associated with CIRs and pure HSSs (47.9%), followed by MCs and noncloud ICMEs (20.6%), pure sheath fields (10.8%), and sheath and ICME combined occurrence (9.9%). In terms of solar cycle dependence, CIRs and HSSs are the dominant drivers in the declining phase and at solar minimum. CIRs and HSSs combined have about the same level of importance as ICMEs plus their sheaths in the rising and maximum solar cycle phases. Thus, CIRs and HSSs are the main driver of moderate storms throughout a solar cycle but with variable contributions from ICMEs, their shocks (sheaths), and combined occurrence within the solar cycle. This result is significantly different than that for intense ( Dst ≤ −100 nT) and superintense ( Dst ≤ −250 nT) magnetic storms shown in previous studies. For superintense geomagnetic storms, 100% of the events were due to ICME events, while for intense storms, ICMEs, sheaths, and their combination caused almost 80% of the storms. CIRs caused only 13% of the intense storms. The typical interplanetary electric field ( Ey ) criteria for moderate magnetic storms were identified. It was found that ~80.1% of the storms follow the criterion of Ey ≥ 2 mV m −1 for intervals longer than 2 h. It is concluded that southward directed interplanetary magnetic fields within CIRs/HSSs may be the main energy source for long‐term averaged geomagnetic activity on Earth. Key Points: The interplanetary origins of moderate storms are studied This study is conducted over a full solar cycle The results are compared with those of intense storms